Fear of movement (kinesiophobia) after cardiac hospitalization: predictors and impact on participation in cardiac rehabilitation. (11th May 2022) - Keessen, P; Visser, B; Van Duijvenbode, ICD; Latour, CHM; Jorstad, HT; Scholte Op Reimer, WJM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch Research Council (NWO) RAAK-PRO grant Background: Fear of movement (kinesiophobia) after cardiac hospitalization is associated with low physical activity levels and reduced quality of life. Participation in cardiac rehabilitation (CR) improves psychological wellbeing and relieves kinesiophobia. However, little is known about the predictors of kinesiophobia and the impact of kinesiophobia on participation in CR. Purpose: To identify predictors of kinesiophobia after (acute) cardiac hospitalization and to assess the impact of kinesiophobia on participation in CR. Methods: We performed a longitudinal study in patients with coronary artery disease, acute heart failure or atrial fibrillation. At hospital discharge we collected demographic variables, cardiac disease history and administered questionnaires about kinesiophobia, cardiac anxiety, depression and psychological complexity (severity of psychological problems). Kinesiophobia was measured with the Tampa Scale for Kinesiophobia (TSK), scores >28 are considered `high levels of kinesiophobia'. At 3 months patients were followed up to evaluate participation in CR. We investigated (1) predictors of kinesiophobia at hospital discharge and (2) the impact of kinesiophobia on participation in CR at 3-months follow up, using two multivariable logistic regression models with backward elimination to identify predictors. Results: In 149 patients (22% women), mean age 64.1 (±10.1) high levels of kinesiophobia were measured in 61 patients (40, 9%). Higher age decreased the odds for kinesiophobia: OR: 0.95 (95%CI:0.89 – 0.99). Two variables increased the odds for kinesiophobia: higher levels of psychological complexity: OR: 1.27 (95%CI 1.01- 1.60) and cardiac anxiety: OR: 1.10 (95%CI: 1.02 – 1.19). The odds for participating in CR were decreased by kinesiophobia: OR: 0.91 (95%CI: 0.84 – 0.99) and higher age: OR: 0.92 (95%CI:0.86-0.98). Conclusion(s): Kinesiophobia at hospital discharge is associated with psychological complexity and negatively impacts participation in CR. This study emphasizes the need for early screening to identify those who are at risk of developing kinesiophobia which in turn can lead to non-adherence to CR.